First-Principle Studies of the Structural, Electronic, and Optical Properties of Double-Walled Carbon Boron Nitride Nanostructures Heterosystem under Various Interwall Distances - Yahaya Saadu Itas; Abdussalam Balarabe Suleiman; Chifu E. Ndikilar; Abdullahi Lawal; Razif Razali; Ismail Ibrahim Idowu; Mayeen Uddin Khandaker; Amina Muhammad Danmadami; Pervaiz Ahmad; Talha Bin Emran; Mohammad Rashed Iqbal Faruque (Journal of Chemistry)
Structural, electronic, and optical properties of a new combined system of carbon and boron nitride nanotubes are studied using the DFT first principles as implemented in Quantum ESPRESSO codes. The corrections to the quasi-particle energies were studied via GW hybrid functional implemented in the YAMBO code within the many-body perturbation theory. The studies were performed under different interwall distances of 3.0 nm, 2.5 nm, and 1.5 nm between CNTs and BNNTs. The results showed that the structural properties demonstrated high stability of the double-walled carbon boron nitride nanotube (DWCBNNT) systems under interwall distance (IWD) of 3.00 nm, 2.50 nm, and 1.50 nm. Results also demonstrated an inverse variation between the IWD and the diameter of the DWCBNNT system. In terms of the electronic properties, all three configurations of the DWCBNNTs reveal semiconducting behavior under KS-DFT showing a direct band gap of 3.30 eV, 1.79 eV, and 0.81 eV under IWD of 3.0 nm, 2.5 nm, and 1.5 nm, respectively. Furthermore, the band gap of the DWCBNNT increases with an increase in IWD (decrease in inner tube diameter) and decreases with a decrease in IWD (increase in inner tube diameter). In all three cases, the bands are formed by the molecular orbitals of the armchair CBNNT which are transformed to a series of continuous energy levels; the behaviors of electrons that formed the heterostructure are related to the behavior of electrons in B, C, and N atoms. From the optical properties perspective, the studies were conducted in parallel and perpendicular directions to the nanotubes’ axes. The presence of static dielectric functions in parallel direction at 3.3, 3.4, and 4.5 for nanotubes under 3.0 nm, 2.5 nm, and 1.5 nm demonstrated optical refraction. Refractions were also observed in directions perpendicular to the nanotubes. Furthermore, optical reflections occur when there is a higher absorption. The ability of these CBNNT hybrid systems to refract in all directions revealed the most exciting properties of the armchair CBNNT suitable to be used in magnifying glass materials. The findings further imply that the optical absorption coefficient is inversely related to the diameter of the nanotubes and is directly correlated to the band gap.